MELTING RELATIONS OF PERIDOTITE AND THE DENSITY CROSSOVER IN PLANETARY MANTLES - Ohtani E.; Nagata Y.; Suzuki A.; Kato T. (My University, 1995)
Melting relations of primitive peridotite were studied up to 25 GPa. The change of the liquidus phase from olivine to majorite occurs at # 16 GPa. We confirmed the density crossover of the FeO-rich peridotite melt and the equilibrium olivine (Fo90) at # 7 GPa. Sinking of equilibrium olivine (Fo95) in the primitive peridotite melt was observed up to 10 GPa. The compression curves of FeO-rich peridotitic and komatiite melts reported in this and earlier work suggest that the density crossover in the Earth's mantle will be located at # 11-12 GPa at 2000°C, consistent with an previous estimation by C.B. Agee and D. Walker.The density crossover can play a key role in the Moon and the terrestrial planets, such as the Earth, Venus and Mars. Majorite and some fraction of melt could have separated from the ascending diapir and sunk downwards at the depths below the density crossover. This process could have produced a garnet-rich transition zone in the Earth's mantle. The density crossover may exist in the FeO-rich lunar mantle at around the center of the Moon. The density crossover which exists at the depth of # 600 km in the Martian mantle plays a key role in producing a fractionated mantle, which is the source the parent magmas of the SNC meteorites.